2013
DOI: 10.1063/1.4804994
|View full text |Cite
|
Sign up to set email alerts
|

Effect of excited states on the ground-state modulation bandwidth in quantum dot lasers

Abstract: We consider direct and indirect (excited-state-mediated) capture of carriers from the waveguide region into the lasing ground state in quantum dots (QDs) and calculate the modulation response of a QD laser. We show that, when only indirect capture is involved, the excited-to-ground-state relaxation delay strongly limits the ground-state modulation bandwidth of the laser—at the longest tolerable relaxation time, the bandwidth becomes zero. When direct capture is also involved, the effect of excited-to-ground-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…Modulation bandwidths are also strongly dependent on the scattering scheme, as was reported in Ref. 12. The authors found indirect, ES-mediated capture processes to be detrimental to GS bandwidth.…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…Modulation bandwidths are also strongly dependent on the scattering scheme, as was reported in Ref. 12. The authors found indirect, ES-mediated capture processes to be detrimental to GS bandwidth.…”
mentioning
confidence: 58%
“…[6][7][8] Nonetheless, due to their low threshold currents, high temperature stability, and high efficiency, 9 studying their dynamic properties is still the topic of many recent publications. 1,[10][11][12][13] Moreover, QDs also exhibit some unique lasing behavior, setting them apart from other gain materials. Because of their effectively zero-dimensional structure, electronic states are quantized in a quasi-atom-like fashion, giving rise to multiple well separated energy levels.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…В КТ достаточно большого размера существует значительное количество электронных и дырочных уровней, которые формально могут соответствовать большому количеству возбужденных состояний [14]. Однако вероятность перехода с большинства этих возбужденных состояний на основанное состояние довольно мала [15] вследствие правил отбора. В то же время интенсивность пика возбужденного состояния может значительно возрастать, если его энергия отстоит от энергии основного состояния на кратное число LO-фононов, что значительно облегчает релаксацию носителей.…”
Section: экспериментunclassified
“…For the theoretical model used in the study, three states including GS, ES, and wetting layer (WL) are considered in the QD laser. 15,17,18 It is assumed that the downward carriers in the WL can be either directly captured into the GS or excited-state-mediated. The carriers also can escape back to the WL via those two ways.…”
mentioning
confidence: 99%